Hubungan Stress dengan Siklus Menstruasi Remaja di SMA Bhinneka Karya 2: The Relationship between Stress and Teen Menstrual Cycle at Bhinneka Karya 2 High School - Rustiannisa Rismatiti; Liyanovitasari (Journal of Holistics and Health Sciences (JHHS), 2022)
Entering puberty in adolescent girls causes psychological changes that cause adolescents to tend to experience stress. Stress that arises in adolescents causes changes in adolescent female hormone levels so that there are frequent disturbances in the menstrual cycle. To determine the relationship between stress and menstrual cycles in adolescents at Bhinneka Karya High School. This study used a quantitative method, the research design used was descriptive correlation, with a cross sectional approach. The population of this study were all female students at Bhinneka Karya 2 Boyolali High School, totaling 96 female students. The sampling technique used was the total sampling method with a sample size of 96 respondents. The measuring instrument used is the Perceived Stress Scale (PSS) questionnaire. Data analysis using Chi Square test. The results of the univariate analysis of stress and menstrual cycle variables showed that 63.5% of respondents experienced moderate stress and 54.2% experienced menstrual cycle disorders. Based on the results of the analysis with the Chi Square test, the p-value is 0.00 < 0.05 (α). There is a relationship between stress and the menstrual cycle in adolescents at Bhinneka Karya 2 High School. Suggestion: It is hoped that further researchers can develop the results of this study by considering variables that can affect the menstrual cycle other than stress levels. ABSTRAK Memasuki masa pubertas pada remaja putri menimbulkan perubahan psikologis yang mengakibatkan remaja cenderung mengalami stress. Stress yang timbul pada remaja menyebabkan perubahan kadar hormon kewanitaan remaja sehingga sering terjadi gangguan pada siklus menstruasi. Mengetahui hubungan stres dengan siklus menstruasi pada ramaja di SMA Bhinneka Karya. Penelitian ini menggunakan metode kuantitatif, desain penelitian yang digunakan adalah deskriptif korelasional, dengan pendekatan cross sectional. Populasi penelitian ini adalah semua ramaja putri di SMA Bhinneka Karya 2 Boyolali yang berjumlah 96 ramaja putri. Teknik pengambilan sampel menggunakan metode total sampling dengan jumlah sampel 96 responden. Alat ukur yang digunakan adalah kuesioner Perceived Stress Scale (PSS). Analisis data menggunakan uji Chi Square. Hasil : Hasil analisis univariat variable stress dan siklus menstruasi didapatkan hasil memperoleh bahwa 63.5% responden mengalami stress sedang dan 54.2% mengalami gangguan siklus menstruasi. Berdasarkan hasil analisis dengan uji Chi Square diperoleh memperoleh nilai p-value sebesar 0.00< 0.05 (α). Terdapat hubungan stress dengan siklus menstruasi pada ramaja di SMA Bhinneka Karya 2 Diharapkan peneliti selanjutnya dapat mengembangkan hasil penelitian inidengan mempertimbangkan varibel yang dapat mempengaruhi siklus menstruasi selain tingkat stress.